2002
DOI: 10.1074/jbc.m112439200
|View full text |Cite
|
Sign up to set email alerts
|

Calcium-independent and cAMP-dependent Modulation of Soluble Guanylyl Cyclase Activity by G Protein-coupled Receptors in Pituitary Cells

Abstract: It is well established that G protein-coupled receptors stimulate nitric oxide-sensitive soluble guanylyl cyclase by increasing intracellular Ca 2؉ and activating Ca 2؉ -dependent nitric-oxide synthases. In pituitary cells receptors that stimulated adenylyl cyclase, growth hormonereleasing hormone, corticotropin-releasing factor, and thyrotropin-releasing hormone also stimulated calcium signaling and increased cGMP levels, whereas receptors that inhibited adenylyl cyclase, endothelin-A, and dopamine-2 also inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 52 publications
1
16
0
Order By: Relevance
“…Furthermore, here we showed that inhibition of phosphodiesterases by IBMX led to facilitation of pacemaking in somatotrophs. This treatment elevates both cAMP and cGMP concentrations in pituitary cells, reflecting intrinsic activity of adenylyl cyclase and soluble guanylyl cyclase (Kostic et al 2002). In our hands, GHRH also stimulated pacemaking, and it is well established that this agonist enhances cAMP and cGMP production (Kostic et al 2004;Lussier et al 1991;Tomic et al 1999a), which in turn activates TTX-insensitive cation channels that predominantly conduct Na ϩ (Kato and Sakuma 1997;Kato et al 1992;Lussier et al 1991).…”
Section: Discussionmentioning
confidence: 76%
“…Furthermore, here we showed that inhibition of phosphodiesterases by IBMX led to facilitation of pacemaking in somatotrophs. This treatment elevates both cAMP and cGMP concentrations in pituitary cells, reflecting intrinsic activity of adenylyl cyclase and soluble guanylyl cyclase (Kostic et al 2002). In our hands, GHRH also stimulated pacemaking, and it is well established that this agonist enhances cAMP and cGMP production (Kostic et al 2004;Lussier et al 1991;Tomic et al 1999a), which in turn activates TTX-insensitive cation channels that predominantly conduct Na ϩ (Kato and Sakuma 1997;Kato et al 1992;Lussier et al 1991).…”
Section: Discussionmentioning
confidence: 76%
“…Additionally, elevations in cAMP affect exocytosis (Renström et al, 1997; Sikdar et al, 1998; Cochilla et al, 2000; Kostic et al, 2002; Sedej et al, 2005; Gonzalez-Iglesias et al, 2006), but it is less clear exactly which exocytic stages are modulated by cAMP. In lactotrophs, cAMP facilitates hormone release via several mechanisms (Gonzalez-Iglesias et al, 2006, 2008; Stojilkovic et al, 2010), also by affecting the exocytic machinery (Sikdar et al, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…Anterior pituitaries were removed from adult female Sprague-Dawley rats obtained from Tacoma Farms (Germantown, NY, USA) and dispersed as described previously (Kostic et al 2002). Dispersed cells were cultured for 24 h in medium 199 containing Earle's salts, sodium bicarbonate, 10% horse serum, and penicillin (100 U/ml) and streptomycin (100 mg/ml).…”
Section: Cell Culturesmentioning
confidence: 99%